1979
DOI: 10.1002/mus.880020612
|View full text |Cite
|
Sign up to set email alerts
|

Letters to the editor

Abstract: We concur with the findings of Streib, Miilbourn, and Mitsunioto' that fibrillation potentials (FPs) are most. frequently found in paraspinal muscles in patients with polymyositis or dermatomyositis or both, and we wish to eInpliasize that the degree of electrical and histologic abnormality may be greatest in these muscles as well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…Furthermore, a training session where the raters agreed on how to interpret the NINDS scale as carried out by Litvan et al was not performed in the present study, because the aim was to imitate real-life conditions. Accordingly, a study by Manschot et al that was conducted using raters with a more heterogeneous professional background than in the study by Litvan et al reported far lower kappa values, ranging from slight to moderate, comparable with those obtained in the present study 6 . Both interrater agreement and intrarater agreement were found to be the lowest for the test of the BRR.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…Furthermore, a training session where the raters agreed on how to interpret the NINDS scale as carried out by Litvan et al was not performed in the present study, because the aim was to imitate real-life conditions. Accordingly, a study by Manschot et al that was conducted using raters with a more heterogeneous professional background than in the study by Litvan et al reported far lower kappa values, ranging from slight to moderate, comparable with those obtained in the present study 6 . Both interrater agreement and intrarater agreement were found to be the lowest for the test of the BRR.…”
Section: Discussionsupporting
confidence: 82%
“…Studies assessing its validity in the detection of C8 and T1 nerve root and proximal median nerve lesions such as the anterior interosseus syndrome are now needed 6 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations